Magnetically-actuated hydrogel-based achiral planar microswimmers for SERS detection: In situ coprecipitation for continuous loading of iron oxide nanoparticles - Xiong, Junfeng; Zhang, Junkai; Zhong, Yukun; Song, Xiaoxia; Wang, Haoying; Cheang, U Kei (Frontiers in Bioengineering and Biotechnology, 2023)
Ultraviolet lithography is a very promising technology used for the batch fabrication of biomedical microswimmers. However, creating microswimmers that can swim at low Reynolds number using biocompatible materials while retaining strong magnetic properties and excellent biomedical functionality is a great challenge. Most of the previously reported biomedical microswimmers possess either strong magnetic properties by using non-biocompatible nickel coating or good biocompatibility by using iron oxide particle-embedded hydrogel with weak magnetism, but not both. Alternatively, iron oxide nanoparticles can be coated on the surface of microswimmers to improve magnetic properties; however, this method limited the usability of the microswimmers’ surfaces. To address these shortcomings, this work utilized an in situ synthesis technique to generate high magnetic content inside hydrogel-based achiral planar microswimmers while leaving their surfaces free to be functionalized for SERS detection. The hydrogel matrices of the magnetically actuated hydrogel-based microswimmers were first prepared by ultraviolet lithography. Then, the high concentration of iron oxide was achieved through multiple continuous in situ coprecipitation cycles. Finally, the SERS detection capability of magnetically actuated hydrogel-based microswimmers was enabled by uniformly growing silver nanoparticles on the surface of the microswimmers. In the motion control tests, the microswimmers showed a high swimming efficiency, high step-out frequency, and consistent synchronized motion. Furthermore, the magnetically actuated hydrogel-based microswimmers were able to improve the detection efficiency of analytes under magnetic guidance.